Sequencing and Comparative Genomic Analysis of a Highly Metal-Tolerant Penicillium janthinellum P1 Provide Insights Into Its Metal Tolerance - Chi, Bin-Bin; Lu, Ya-Nan; Yin, Ping-Chuan; Liu, Hong-Yan; Chen, Hui-Ying; Shan, Yang (Frontiers in Microbiology, 2021)
Heavy metal pollution is a global knotty problem and fungi hold promising potential for the remediation of wastewater containing heavy metals. Here, a new highly chromium-tolerance species, Penicillium janthinellum P1, is investigated. The genome of P1 was sequenced and assembled into 30 Mb genome size containing 10,955 predicted protein-coding genes with a GC content of 46.16% through an integrated method of Illumina short-read sequencing and single-molecule real-time Pacific Biosciences sequencing platforms. Through a phylogenetic analysis with model species of fungi, the evolutionary divergence time of Penicillium janthinellum P1 and Penicillium oxalicum 114-2 was estimated to be 74 MYA. 33 secondary metabolism gene clusters were identified via antiSMASH software, mainly including non-ribosomal peptide synthase genes and T1 polyketide synthase genes. 525 genes were annotated to encode enzymes that act on carbohydrates, involving 101 glucose-degrading enzymes and 24 polysaccharide synthase. By whole-genome sequence analysis, large numbers of metal resistance genes were found in strain P1. Especially ABC transporter and Superoxide dismutase ensure that the P1 fungus can survive in a chromium-polluted environment. ChrA and ChrR were also identified as key genes for chromium resistance. Analysis of their genetic loci revealed that the specific coding-gene arrangement may account for the fungus’s chromium resistance. Genetic information and comparative analysis of Penicillium janthinellum are valuable for further understanding the mechanism of high resistance to heavy metal chromium, and gene loci analysis provides a new perspective for identifying chromium-resistant strains.